NILAI-NILAI FILOSOFIS HUMA BETANG SUKU DAYAK KALIMANTAN TENGAH - Heva Rostiana; Siti Nurbani; Dody Riswanto (Universitas PGRI Adi Buana Surabaya, 2020)
The Dayak tribe in Central Kalimantan has a traditional custom house called the Huma Betang. Huma Betang is a stilt-shaped house that extends and can be inhabited by hundreds of people. Huma Betang is not only seen as a physical building, but also contains philosophical values contained in it. The purpose of this study is to discover the philosophical valuesof Huma Betang which are the teachings, traditions and heritage of the ancestors. The research method used is a qualitative approach to data collection techniques,namely interviews, observation, documentation study, and audio-visual information. The results and discussion found a description that the values of the Huma Betang philosophy consisted of 4 main elements namely the value of togetherness, honesty, equality, and tolerance. The implementation of Huma Betang values can be seen in the daily life of Dayak residents such as traditional Tiwah rituals, mutual cooperation, building houses, mutual respect and respect among people of different ethnic, religious, racial, class and cultural backgrounds. Huma Betang has the main function of maintaining harmony and unity of the people of Central Kalimantan for the creation of conditions for a safe, peaceful and harmonious society.